Revision of serum ALT upper limits of normal facilitates assessment of mild liver injury in obese children with non‐alcoholic fatty liver disease. Issue 7 (8th April 2020) - Lu, Yutian; Wang, Qiongdan; Yu, Lisha; Yin, XueRui; Yang, Huijie; Xu, Xi; Xia, Ying; Luo, Yue; Peng, Ying; Yu, Qigui; Chen, Zhanguo; Yu, Jian; et al.
Abstract: Background: The serum alanine aminotransferase (ALT) level is a critical parameter for evaluating liver injury in non‐alcoholic fatty liver disease (NAFLD). However, the currently accepted upper limits of normal (ULN) for serum ALT (ULN‐ALT) are debated, as they may be excessively high. Methods: A total of 1638 children aged 6‐16 years, comprising 507 children with normal BMI (500 healthy children and 7 children with NAFLD), 199 overweight children, and 932 obese children, were included in the analysis. We re‐evaluated the ULN‐ALT in 500 healthy Chinese children using the 95th percentiles of serum ALT levels as revised ULN‐ALT. Fatty liver was identified by ultrasound examination. Results: Significant positive correlations between serum ALT levels and body mass index (BMI) were detected in overweight boys ( r  = .399, P  < .001), obese boys ( r  = .398, P  < .001), and obese girls ( r  = .392, P  < .001). The prevalence percentages of NAFLD were 93.6%, 75.8%, and 37.9% in obese boys with serum ALT levels of >50, 25‐50, and ≤25 U/L and were 81.6%, 67.9%, and 20.6% in obese girls with serum ALT levels of >40, 20‐40, and ≤20 U/L, respectively. Conclusion: Serum ALT levels significantly correlated with abnormal BMI values in children, suggesting a rigorous BMI threshold is needed to establish the cutoffs for serum ULN‐ALT in children. Besides, the revised serum ULN‐ALT can uncover mild liver injury in obese children with NAFLD.